FIRE RESIDENTIAL PROBLEMS AND SOLUTIONS IN FIRES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Prospects for the use of means of rescuing people in case of fires on multi-storey buildings are considered. The main technical characteristics and the area of effective use of the rescue means are given. The necessity of using rescue equipment from a height in case of fires on multi-story buildings of enterprises and residential complexes in modern conditions is substantiated.